Digital Land Resources to Support Sustainable Development in Egypt Nile Delta, Nile Valley and Promising Desert Areas - Gad, Abd-Alla. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book provides accurate and integrated information about land resources especially with the accelerated progress of information technology to help Egypt and similar countries to achieve the country sustainable development goals in the field of agriculture and natural resources. The Egyptian National sustainable development plans mainly aim to conserve the arable lands in the Nile Delta and the Nile Valley, in addition to the oases and desert fringes. Moreover, increasing land productivity is a vital national goal for filling the food gap. Consequently, providing accurate and integrated information about land natural resources using the recent technologies such as satellite data/images and geoinformatics techniques. Such information would be a base for planning, decision making and research needs all over the world due to the importance of Egypt as the biggest and leading country in the MENA regions. The book provides land natural resources database as a platform, upon which additional thematic information can be added in the future to serve multi approached sustainable development. The book highlights the usage of digital information in monitoring urban planning and encroachment, in addition to soil and land capability classification. Moreover, networks of irrigation/drainages, railways, and utilities are added for a wide management range. Various available information systems were employed to initiate the targeted land resources database (e.g., ArcGIS, ERDAS IMAGINE and ENVI). Data of previous soil survey projects were the basis for the created digital database including High Dam Soil Survey, Soil map of Egypt and Land Master Plane. The Digital Elevation Model (DEM) was elaborated using SRTM space images, in addition to spot heights and contour lines derived from the topographic maps (scale 1:50,000) produced by the Egyptian Survey Authority (ESA). The resulted thematic layers were incorporated in the created GIS land resources database. The book is a unique and a great source of information and knowledge for all researchers around the globe particularly for MENA regions. Researchers, graduate students, the policy planners and decision making will find this book very useful for them. are most people who could benefit from the book. We believe the book will be an added value to the existing information and knowledge.
Chapter 1. Introduction -- Chapter 2. Materials Used -- Chapter 3. Methodology -- Chapter 4. Results and Discussion. .
Keywords: Sustainability; Water; Hydrology; Mining engineering; Sustainability; Water; Mining and Exploration